Critical Discourse Analysis of Sunda Empire Case in The Indonesia Lawyers Club Panel Discussion - Gin gin Ginanjar (Jambura Journal of Linguistics and Literature, 2022)
Critical discourse analysis is method and theory used in empirical review on correlations between discourse and development in social and cultural aspect. This research aimed to describe the text analysis, social cognition and context in the Sunda Empire discourse for the Indonesia Lawyer Club Panel Discussion. The data and data source consists of oral discourses by experts from the recorded episode of Indonesia Lawyers Club broadcasted on January 21st, 2020 with the topic of “Siapa dibalik Raja-raja Baru?”. The text analysis found macrostructure, superstructure, and microstructure while the social cognition analysis found schemes of person, self, role and event. Lastly, the social context analysis fiund development of the discourse by Rangga Sasana as the informant of Sunda Empire at the Panel Discussion to the entire participating experts and every Indonesian people, which is based on the amount of digital news that discussed statements from the discourse.